The effectiveness of biogas liquid waste originated from palm oil industry to produce Chlorella sp. in the outdoor scale - Puspita Wulan Sari; M. Hasbi; T. Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The biogass liquid waste originated from palm oil industry contains high nutrient and it can be used for growing microalgae such as Chlorella sp. To understand the effectiveness of the waste as a medium to grow Chlorella sp., a study was conducted from September – October 2016. The culture was conducted in the outdoor scale. There were 4 treatments applied, namely P0 (0% waste), P1 (15% waste), P2 (20% waste), and P3 (25% waste). Parameters measured were the abundance and the biomass of Chlorella sp., nitrate and phosphate content, pH, TDS, and temperature. Results shown that the best growth of Chlorella sp. was in the P1, the abundance was 7,252,800 cells/ml and the biomass was 3.51 gr/L. The growth of Chlorella sp. was able to reduce the nitrate and phosphate concentration, from 11.1 to 1.51 mg/l (nitrate) and from 0.617 to 0.033 mg/l (phosphate) respectively. This fact indicates that the nutrient have been used for growing the microalgae. Based on data obtained, it can be concluded that the palm oil liquid waste can be used as nutrient source for Chlorella sp.Key words : palm oil industry liquid waste, nutrient, microalgae, Chlorella sp.